Artistic Development as a Process of Universal-Relative Selection Possibilities - Hamblen, Karen A. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
The assumptions of stage theory and major theories of child art are reviewed in order to develop an explanation of artistic expression that allows for variable endpoints and accounts for relationships between children's drawings and adult art. Numerous studies indicate strong similarities among children's early drawings, which suggests that primarily universal factors of influence are operative. Cross-cultural similarities and differences among adult art suggest that universal factors are still operative although relative factors predominate. A model of artistic selection possibilities is developed based on the premise that art consists of options selected from universal and relative domains, circumscribed by the imperatives of time, place, and level of skill acquisition. Similarities and differences between child and adult art as well as variable personal and cultural endpoints are accounted for when artistic development can be described as a selection process rather than a step-by-step predefined progression. (Author/KC)
ERIC Note: Paper presented at the National Symposium for Research in Art Education (Champaign-Urbana, IL, October 2-5, 1984).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adults; Age Differences; Art Education; Art Expression; Biological Influences; Child Development; Childrens Art; Cultural Context; Cultural Influences; Developmental Stages; Social Influences; Talent Development; Opinion Papers; Information Analyses; Speeches/Meeting Papers